Layered Sexism in The Accused - Annette Prizyllia Siahaan; Rasus Budhyono; Lestari Manggong (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2023)
The Accused (1988), a movie adaptation of a real-life event about a gang-raped victim who seeks justice, depicts sexist behavior towards the survivor during the trial. With the main premise of seeking justice for a rape survivor, this movie highlights Sarah’s experience to gain justice through a sexist masculine institution. Referring to the theory of sexism by Manne, this article aims to show how this movie shows sexist behavior toward the survivor during law enforcement. Dialogues that show sexism between characters are used in the analysis of the movie's plot, then used to discuss the portrayal of sexism in The Accused from a feminist point of view. From the dialog and the portrayal of layered sexism, we find that as a movie promoting human rights, The Accused still implies that a woman who does not meet the expected gender roles is undeserving of justice. As a result, a ‘bad’ woman as a victim whose experience is reduced is seen as a norm.